The Effect of Changes in the Storage Temperature and Acceptability of Animal-Based Food Ingredients in the Refrigerated Room of HODASCO 19 - Wahyu Satrio Tegar; Antonius Edy Kristiyono; Prima Yudha Yudianto; Agus Prawoto; Shofa Dai Robbi (Maritime Park: Journal of Maritime Technology and Society, 2026)
This study examined how refrigerated-room temperature affected the acceptability of animal-based food ingredients (chicken, beef, and fish) stored on board HODASCO 19. The study used a descriptive quantitative design based on organoleptic observation. Five assessors evaluated odour, colour, and texture using a five-point Likert scale for samples stored at −18 °C, 0 °C, and 4 °C over four weeks. Mean scores were calculated and interpreted using fixed acceptability intervals. The results show a clear temperature effect. Storage at −18 °C maintained the highest acceptability throughout the observation period, with mean scores remaining in the very acceptable category (4.86–5.00). Storage at 0 °C showed the sharpest decline, dropping from very acceptable at week 0 to unacceptable by week 2 and highly unacceptable by weeks 3–4. Storage at 4 °C performed better than 0 °C in this onboard dataset but still declined from very acceptable at week 1 to moderately acceptable at week 3 and unacceptable at week 4. The findings confirm that low and stable storage temperatures are essential for preserving the quality of perishable animal-based food ingredients on board ships. Practically, the refrigerated room should be maintained as close as possible to −18 °C for longer storage, while short-term storage at higher temperatures requires stricter monitoring.